Type I Interferons Modulate CD8+ T Cell Immunity to mRNA Vaccines. Issue 3 (March 2017) - De Beuckelaer, Ans; Grooten, Johan; De Koker, Stefaan
Abstract : mRNA vaccines have emerged as potent tools to elicit antitumor T cell immunity. They are characterized by a strong induction of type I interferons (IFNs), potent inflammatory cytokines affecting T cell differentiation and survival. Recent reports have attributed opposing roles for type I IFNs in modulating CD8+ T cell immunity to mRNA vaccines, from profoundly stimulatory to strongly inhibitory. The mechanisms behind this duality are unclear. Disentangling the factors governing the beneficial or detrimental impact of type I IFNs on CD8+ T cell responses is vital to the design of mRNA vaccines of increased potency. In light of recent advancements regarding the complex role of type I IFNs in regulating CD8+ T cell immunity to infectious diseases, we posit that the dual outcome of type I IFNs on CD8+ T cell responses to mRNA vaccination is determined by the timing and intensity of type I IFN induction relative to T cell receptor (TCR) activation. Trends: Antigen-encoding mRNA vaccines (e.g., against tumors) exhibit a high capacity to elicit cytolytic CD8 + T cells, with a unique capacity to destroy cancer (or virally infected) cells. mRNA vaccines elicit a profound type of I IFN response and specific signature. Type I IFNs can have either a beneficial or a detrimental impact on CD8 + T cell immunity. Type I IFNs can promote CD8 + T cell responses to systemic mRNA vaccination yet interfere with topical (intradermal/subcutaneous) mRNA vaccination. The functional repercussions of type I IFNs on the magnitude and quality of elicited CD8 + T cell responses are a topic of intense debate. The dual effects of type I IFNs on antiviral CD8 + T cell immunity are largely determined by the relative kinetics of type I IFN signaling to T cell receptor (TCR) activation. Based on these findings, we argue that similar mechanisms govern the impact of type I IFNs on the CD8 + T cell response to mRNA vaccines.